Simultaneous spontaneous pneumothorax and colonic perforation in a patient with rectosigmoid carcinoma with metastases: A complex multisystem presentation - Anbumani, Prasanth; Arayamparambil Vijayan, Padmakumar; K Manjunatha, Ganesh; Kuraning, Kiran; Suresh Chandan, Garud; Prathapan Sarada, Pooja (Indian Journal of Case Reports, 2026)
Rectosigmoid carcinoma commonly presents with complications such as bowel obstruction, bleeding, and perforation. Spontaneous pneumothorax in patients with colorectal cancer (CRC) is rare and is usually associated with pulmonary metastases or chemotherapy-related lung injury. The simultaneous occurrence of spontaneous pneumothorax and malignant colonic perforation is exceptionally uncommon and poses significant diagnostic and therapeutic challenges. We report the case of a 71-year-old man with metastatic rectosigmoid adenocarcinoma on second-line chemotherapy who presented with per-rectal bleeding and subsequently developed sigmoid colon perforation with feculent peritonitis along with a concomitant spontaneous pneumothorax. The patient required urgent thoracic and abdominal interventions, intensive post-operative care, and coordinated multidisciplinary management. This case highlights the importance of the early recognition of rare synchronous complications in advanced CRC and emphasizes the role of prompt surgical and supportive management in achieving clinical stabilization.